Dynamic analysis of three degree of freedom (3-DOF) exoskeleton for lower extremities - Mohd Zawawi, M.Z.F. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper shows the step by step kinematic and dynamic derivation for three degree of freedom exoskeleton for lower extremities. By using the Denavit Harternberg theorem, the forward and inverse kinematic solutions of the exoskeleton are performed. The Lagrange mathematical statement is utilized which talks about kinetic strength and potential strength amid maneuver. The Anthropometry of the proposed exoskeleton design is computed by using Dempster, Clauser and Chandler method. This outcome can be used in control design for the proposed prototype lower extremities exoskeleton. © 2016 IEEE.